How does Government Support Affect Primary Employment by Entrepreneurs in US States? - KAYA, Halil D. (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
In this study, we examine if government support to entrepreneurs in US states affects the ‘type of entrepreneurship’ in these states. We differentiate between ‘full-time entrepreneurs’ who has their business as their primary employment and ‘part-time entrepreneurs’ who has their business as their secondary job or hobby. Our hypothesis is that more government support would help entrepreneurs so that they would not need to direct all of their time, energy, and focus on their small business. Our results show that, although there are more ‘part-time entrepreneurs’ in the states with relatively more government support for entrepreneurs, the results are statistically insignificant. Therefore, we can conclude that government support in a state generally does not alter the ‘type of entrepreneurship’ in that state.